Toward a more embedded/extended perspective on the cognitive function of gestures - Pouw, Wim T. J. L.; de Nooijer, Jacqueline A.; van Gog, Tamara; Zwaan, Rolf A.; Paas, Fred (Frontiers in Psychology, 2014)
Gestures are often considered to be demonstrative of the embodied nature of the mind (Hostetter & Alibali, 2008). In this article we review current theories and research targeted at the intra-cognitive role of gestures. We ask the question how can gestures support internal cognitive processes of the gesturer? We suggest that extant theories are in a sense disembodied, because they focus solely on embodiment in terms of the sensorimotor neural precursors of gestures. As a result, current theories on the intra-cognitive role of gestures are lacking in explanatory scope to address how gestures-as-bodily-acts fulfill a cognitive function. On the basis of recent theoretical appeals that focus on the possibly embedded/extended cognitive role of gestures (Clark, 2013), we suggest that gestures are external physical tools of the cognitive system that replace and support otherwise solely internal cognitive processes. That is gestures provide the cognitive system with a stable external physical and visual presence that can provide a platform to think on. We show that there is a considerable amount of overlap between the way the human cognitive system has been found to use its environment, and how gestures are used during cognitive processes. Lastly, we provide several suggestions of how to investigate the embedded/extended perspective of the cognitive function of gestures.